ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS BATAKO DENGAN MENGGUNAKAN METODE TAGUCHI -KANO - Setyawan, Widy; Saefurrohman, Iman (Universitas Suryakancana, 2018)
Abstract— Quality is one thing that is important in the face of competition in the industry. An industry that can produce a product or service with good quality have a greater opportunity to compete. Customer satisfaction is the most important thing to know if the quality of a product can be accepted in the market or not, the customer satisfaction in the mean is how the compressive strength and absorption of tiles made at the plant WS is already in line with consumer expectations or not. This study aims to mengeathui customers are satisfied or not with the quality of bricks produced. The method used in this study using a model Kano with the results, test the validity of the first statement obtained r count of 0471 and the value of r table at 0294. reliability test results with Crombach's Alpha 0709 of 13 N of the item. Kano categorization results obtained category I (indifferent) and R (Reverse), which means indefferent is neutral, the dimensions of Reliability quality brick is good but it would be nice if it improved again. And on the dimensions showed Responsive service and the level of customer satisfaction with quality brick beraada at the level of R (Reverse), which means a setback, at this level that the quality of tiles made the necessary level.